Beispiel Nr: 19
$ \text{Gegeben:} ax^{2}+bx+c=0 \\ \text{Gesucht:} \\ \text{Lösung der Gleichung} \\ \\ ax^{2}+bx+c=0 \\ \textbf{Gegeben:} \\ x^2-4x+7 =0 \\ \\ \textbf{Rechnung:} \\ \begin{array}{l|l|l} \begin{array}{l} \text{a-b-c Formel}\\ \hline 1x^{2}-4x+7 =0\\ x_{1/2}=\displaystyle\frac{+4 \pm\sqrt{\left(-4\right)^{2}-4 \cdot 1 \cdot 7}}{2\cdot1}\\ x_{1/2}=\displaystyle \frac{+4 \pm\sqrt{-12}}{2}\\ \text{Diskriminante negativ keine Lösung} \end{array}& \begin{array}{l} \text{p-q Formel}\\ \hline \\ \\ x^{2}-4x+7 =0 \\ x_{1/2}=\displaystyle -\frac{-4}{2}\pm\sqrt{\left(\frac{\left(-4\right)}{2}\right)^2-7} \\ x_{1/2}=\displaystyle 2\pm\sqrt{-3} \\ \text{Diskriminante negativ keine Lösung} \end{array}\\ \end{array}$